MOTIVATION AND STIMULATION OF EFFECTIVE TEACHING AND LEARNING PROCESS - I. V. Boiko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2015)
This article deals with the methods of motivation and stimulation of successful teaching and learning process in higher education, their role in the education system and the impact on the educational process itself, as well as the full development of student's personality. The basic methods of encouragement and disciplinary actions of students in learning, their theoretical justification and features of the practical application of science teaching were investigated. The article presents a classification of the main motives for learning and personal development of students in the higher education. It also examines the main types of pedagogic assessment, namely substantive and personal, material and moral, and effective procedural, quantitative and qualitative types of pedagogic assessment. Along with the types of educational assessments, the ways to stimulate learning and educational success are determined, chief among them: attention, approval, recognition, assessment, and support, reward, increasing social role, prestige and status of the student as a person. Each of these methods of stimulation is considered separately. The article highlights the methods of stimulation and motivation, which are divided into two main groups, namely methods of formation of cognitive interests and methods of formation of the sense of duty and responsibility in education. Methods of formation of cognitive interest include: creating a situation in class curiosity - an introduction to the learning process of certain interesting examples of experiments and paradoxical facts, usage of interesting analogies, creating a situation of novelty, relevance, making up game situations in the classroom, educational discussion, stimulation with analysis of life situations, creating success in learning situations. Methods aimed at creating a sense of duty and responsibility in education include the nomination of educational requirements and encouragement of learning and condemnation.